Literature at the service of truth: Simone Weil and 'L’Enracinement' - Doering, E. Jane (Labyrinth, 2023)
The purpose of this article is to elaborate the many literary allusions that Simone Weil used in her ultimate work: L' Enracinement, translated as The Need for Roots, to achieve her goal of encouraging her fellow countrymen to create a new postwar society. Understanding how she used the riches of the French and Western Literary Cannon, less easily grasped by those not educated in the French Education system, enriches the understanding of Weil's purpose and skill in writing on many levels, simultaneously for different target audiences. Underlying her stress on the need for truth and honesty about a county's past and present, with discernable respect for every person, is her foundational belief in the spiritual destiny of every human being. Examining her literary allusions in detail to show her clever subversion of traditionally accepted interpretations brings a new dimension to Simone Weil studies, while underlining the relevance of this essay to contemporary dilemmas.